2023
DOI: 10.3389/fsurg.2022.1066092
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a nomogram model to predict the overall survival rate of esophageal cancer patients receiving neoadjuvant chemotherapy: A population-based study

Abstract: IntroductionThe development of neoadjuvant chemotherapy(nCT) improves the overall survival (OS) of patients with esophageal cancer(EC). The aim of this study was to determine the independent prognostic factors of EC patients receiving nCT, and to construct a nomogram model for predicting OS.MethodThis retrospective analysis was conducted from the National Cancer Institute's Surveillance Epidemiology and End Results, Clinicopathological data of patients with EC who received nCT from 2004 to 2015. The included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These findings collectively provide compelling evidence that differences in gemcitabine-based nCRT sensitivity predominantly drive the survival disparities between the sexes. Consistent with our results, several studies have reported improved survival outcomes in women with various cancers, including PDAC treated with (neoadjuvant) chemotherapy [24][25][26][27] or nCRT. 28 29 Our comprehensive immune profiling analysis revealed reduced immune suppression as a potential mechanistic basis for the increased efficacy of gemcitabine-based nCRT in PDAC Figure 4 Survival and data exploration analysis in resected PDAC patients included in the transcriptomic Nanostring analysis (A) Kaplan-Meier curves and univariate Cox regression models, stratified by treatment, illustrating the preservation of the significantly prolonged OS in women with resected PDAC who received nCRT compared with men in this patient subset.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings collectively provide compelling evidence that differences in gemcitabine-based nCRT sensitivity predominantly drive the survival disparities between the sexes. Consistent with our results, several studies have reported improved survival outcomes in women with various cancers, including PDAC treated with (neoadjuvant) chemotherapy [24][25][26][27] or nCRT. 28 29 Our comprehensive immune profiling analysis revealed reduced immune suppression as a potential mechanistic basis for the increased efficacy of gemcitabine-based nCRT in PDAC Figure 4 Survival and data exploration analysis in resected PDAC patients included in the transcriptomic Nanostring analysis (A) Kaplan-Meier curves and univariate Cox regression models, stratified by treatment, illustrating the preservation of the significantly prolonged OS in women with resected PDAC who received nCRT compared with men in this patient subset.…”
Section: Discussionsupporting
confidence: 92%
“…[20][21][22][23] Multiple studies have consistently reported better response rates and prolonged survival among women undergoing anticancer treatments, including nCRT. [24][25][26][27][28][29] Inititally, these beneficial outcomes were ascribed to reduced exposure to risk factors or enhanced pharmacokinetic drug handling. However, accumulating evidence underscores the role of sex-dependent immunity.…”
Section: Introductionmentioning
confidence: 99%